POLA KOMUNIKASI SISWA SMA PRIDE HOMESCHOOLING DALAM INTERAKSI SOSIAL DI MASYARAKAT - Daffa Izdihar Maulana (2022)
Homeschooling is an alternative education that has a main focus on developing the interests and talents of its students. Learning is also carried out in collaboration between parents and the school. Many people consider one eye of students who attend homeschooling related to their social interaction skills. Based on this, this study aims to analyze how the communication patterns formed by homeschooling students and how their social interactions with attribution theory are used as the basis for identifying causality created in the process of formation. The method used in this study is a qualitative method with a constructivist paradigm that will explain the behavior of homeschooling students based on their experiences. This study shows that the communication pattern carried out by the Pride Homeschooling High School students is a secondary communication pattern in social interaction. Things that affect its formation are based on internal and external factors based on aspects of attribution dimensions in the identification process.